Revision der Gattung Agachila Drake & Gomez-Menor, 1954 (Hemiptera: Heteroptera: Tingidae). - Göllner-Scheiding, Ursula (Contributions to Entomology = Beiträge zur Entomologie, 2012)
The genus Agachila, family Tingidae, is distributed in tropical Africa only. The genus is revised here. Three species Agachila barbarae, A. constanti and A. heinrichae are described as new. The species Agachila biafrana Drake & Gomez-Menor, 1954, is a synonym of Agachila motoensis (Schouteden, 1953). - The genus Agachila and its altogether nine species are characterised. Most of the species live in Central-Africa, only one species in the Republic of South Africa. An identification key and a list of the species is given. Nomenclatural Acts barbarae Göllner-Scheiding, 2012 (Agachila), spec. nov. biafrana Drake & Gomez-Menor, 1954 (Agachila), syn. nov. of Agachila abimva (Schouteden, 1953) constanti Göllner-Scheiding, 2012 (Agachila), spec. nov. heinrichae Göllner-Scheiding, 2012 (Agachila), spec. nov.